KUKUSAN PAKIS JUKUT (Diplazium Esculentum Swartz) PADA KADAR HEMOGLOBIN REMAJA PUTRI - Ramadhanti, Indah Putri; Lubis, Kholilah; Nova, Desri; Putri, Novi Haryani (Jurnal Ilmu Kebidanan, 2023)
Anemia in adolescents is a major global health problem that needs adequate attention. In 2019, the prevalence of anemia among women aged 15-49 worldwide was 29.9%. The prevalence of anemia in Indonesia in 2019 was 84.6% in the adolescent age group (15-24 years). The cause of iron anemia is a lack of hemoglobin in red blood cells. Efforts to reduce the incidence of anemia by increasing iron levels, one of which is the administration of steamed jukut fern containing 291.32 mg of Fe in 100 g of leaves. This study aimed to determine the effect of steaming jukut ferns (Diplazium Esculentum Swartz) on increasing hemoglobin in female adolescents at MAN 1 Model Bukittinggi City in 2020. This type of research was pre-experimental with one group pretest and posttest design. The population of all students of MAN 1 class XII was as many as 20 people, a sample of 10 people with a purposive sampling technique based on inclusion-exclusion criteria. The instrument was an observation sheet. Shapiro Wilc normality test, normally distributed data using paired sample t-test. The results of the univariate analysis were that the mean pretest HB level was 10.080 ± SD 0.4, and the mean posttest Hb level was 11,344 ± SD 0.5. Results of bivariate analysis with p-value = 0.001 (p <0.05). In conclusion, jukut fern steaming affects increasing hemoglobin levels. It is recommended that steaming jukut packs help prevent anemia optimally.